Detección de Salmonella spp. en la superficie de huevos provenientes de gallinas de traspatio, comercializados en las principales ferias libres de la ciudad de Loja, a través del sistema 3M Petrifilm - Casierra Cárdenaz, Angel Alberto (2015)
This research work was conducted in the laboratory of veterinary diagnostic of the “Universidad Nacional de Loja” in order to detect the presence of Salmonella spp. in the surface of hen eggs that belong to the backyard. These eggs are sold in the main fairs from the city of Loja. Through the “3M Salmonella express system”. In total 216 eggs were analyzed the same ones that were grouped in 72 samples (each one made up of three eggs sample). None of the samples confirmed the presence of Salmonella spp. But it was showed lot of mesophilic aerobic bacteria getting average values of 2,59x〖10〗^4 UFC/ml y 1,63x〖10〗^3 UFC/cm^2. Values that may be due to contamination during start due to lack of sanitary control of the nests or during handling, transportation and sale of eggs that may impair their quality and even cause problems in public health; The survey results reveal that 62 % do not perform disinfection in the nests of birds, just as the 62 % does no vaccination in birds and their eggs are stored at room temperature. However, this study does not rule out the presence of Salmonella spp. in eggs marketed in the city of Loja so we recommend continuing related future research. Keywords: salmonella, ufc, eggs, backyard, markets, bacteriology.